2012
DOI: 10.1002/mnfr.201100697
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin induces CYP3A4 expression via pregnane X receptor and CCAAT/enhancer‐binding protein β activation

Abstract: From these data, we conclude that capsaicin induces CYP3A4 expression in vitro and in vivo. This induction was achieved by the activation of hPXR and C/EBPβ. Our results suggest that capsaicin might induce CYP3A4 expression; thus, exposure to capsaicin may increase the metabolism of CYP3A4 substrate and potentially cause food-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…However based on our result, it is plausible to assume that CYP2C9 enzyme in Koreans is rather induced by regular dietary constituents present in Korean food that are not commonly consumed in Sweden. Actually a recent study from Korea reported that capsaicin, the principal pungent ingredient in hot red and chili peppers, induces CYP3A4 expression both in vitro and in vivo via human pregnane X receptor (hPXR) and C/EBPb activation (Han et al, 2012). Another study from Japan also reported the induction of p-glycoprotein (P-gp) by capsaicin (Okura et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However based on our result, it is plausible to assume that CYP2C9 enzyme in Koreans is rather induced by regular dietary constituents present in Korean food that are not commonly consumed in Sweden. Actually a recent study from Korea reported that capsaicin, the principal pungent ingredient in hot red and chili peppers, induces CYP3A4 expression both in vitro and in vivo via human pregnane X receptor (hPXR) and C/EBPb activation (Han et al, 2012). Another study from Japan also reported the induction of p-glycoprotein (P-gp) by capsaicin (Okura et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Another study from Japan also reported the induction of p-glycoprotein (P-gp) by capsaicin (Okura et al, 2010). The authors concluded that regular exposure to dietary ingredient containing capsaicin increases the metabolism of CYP3A4 substrate and P-gp potentially to cause fooddrug interactions ( Han et al, 2012;Okura et al, 2010). Hot red and chili peppers are common spices in regular Korean, Indian, Thai, and Ethiopian food.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inhibition of the TRPV1 receptor demonstrated that release of these neurotransmitters is mediated by a nonselective TRPV1 cation channel , which is permeable to Ca 2+ ions and responsible for triggering dopamine and serotonin release in neural cells . Capsaicin promotes Ca 2+ influx via the TRPV1 cation channel and promotes phosphorylation of the downstream signaling factor Ca 2+ /calmodulin‐dependent protein kinase II , which might be a mechanism of capsaicin‐induced TRPV1 activation. Moreover, capsaicin also stimulates Ca 2+ ‐release from a ryanodine‐sensitive intracellular calcium store .…”
Section: Introductionmentioning
confidence: 99%
“…Capsaicin promotes Ca 2+ influx via the TRPV1 cation channel and promotes phosphorylation of the downstream (1) and nonivamide (2). signaling factor Ca 2+ /calmodulin-dependent protein kinase II [11], which might be a mechanism of capsaicin-induced TRPV1 activation. Moreover, capsaicin also stimulates Ca 2+release from a ryanodine-sensitive intracellular calcium store [12].…”
Section: Introductionmentioning
confidence: 99%